Mission – Oriented Companies in Algeria: Reality and Perspectives - Tafiani Born Boufatah Keltouma (Current Aspects in Business, Economics and Finance Vol. 6, 2022)
New legal forms have emerged over the past ten years or so, in various countries to encourage companies to use their economic performance to serve a mission (social, societal, environmental) defined in the social objective, actionable by stakeholders. An organization with a mission aims to put its economic model and its search for profit in the service of a social or environmental goal based on a generic and transparent mission statement. Camif: It is one of the most important French companies with mission and innovation that successfully accepted this challenge Camif. Some Algerian companies, especially small and medium ones, have already addressed this issue by joining the corporate community with a mission. It brings together leaders who want to include mission as a reason for being in their platform, evaluate it and therefore their progress. We should have a less restricting perspective, and the energies must be liberated, are two of the most crucial prerequisites suggested for the success of this approach in Algeria.